Diagnóstico e tratamento do TDA/H: investigação dos critérios utilizados por diferentes categorias profissionais da cidade de Natal-RN - Aragão, Laura Carolina Lemos (2015)
TDA/H is usually considered among the most frequent psychological malfunctions in both childhood and adolescence. It covers a complex combination of neurocognitive deficits leading to developmental troubles linked to attention failure, hyperactivity and impulsivity. On the other hand, diagnosis of TDA/H is frequently a hard task, since sociocultural aspects concerning the evaluation of symptoms lead to some etiologic vagueness. Additionally, the large extent of evaluation tools, together with the diversity of therapeutic approaches referred by specialized literature justify the interest of investigating the diverse ways of diagnosing and treating TDA/H by medical doctors, psychologists and psycho-pedagogues developing professional activities in Natal-RN (Brazil) in the assistance of children and teenagers with TDA/H diagnosis hypothesis. A sample of thirty-four professionals participated in this study in a convenience-basis, and submitted to a semi-directed interview. Information from this procedure was analyzed, categorized and submitted to a multidimensional descriptive analysis (cluster analysis procedure), allowing to verify the partition of the sample in two groups: Group 1, basically composed by medical professionals, and Group 2, composed by psychologists and psycho-pedagogues. The categorized variable “Number of sessions” – average time used for arriving to a diagnosis – was the partition-variable showing the larger amount of statistical contribution for the partition, followed by the variables “Professional formation” and “Use of diagnostic tools”. Variables such “Comorbidity”, “TDA/H Definition” and Modalities of Intervention” also showed contribution to the partition obtained, even though their lesser amount of statistical contribution. Despite some similarity between these two groups, data allowed to demonstrate specific association between academic source-formation of the professional concerned and diagnosis and intervention modalities shown by these professionals when dealing with TDA/H. These data confirm relevant heterogeneity in dealing with TDA/H due to professional formation of professionals involved in diagnosis and treatment tasks.